THE USE OF SYMBOLS TO SHOW THE MAIN CHARACTER’S PERSONALITY IN THE FAULT IN OUR STARS (Universitas Negeri Semarang, 2023)
As we all know, linguistics is interesting, and it always affects people in many ways. This study tries to uncover the main character’s personality through his/her language use in the novel The Fault in Our Stars by John Green. In this research, linguistic discipline from Ferdinand de Saussure (1916) – Theory of Linguistic Whorf (1956) – Language, Thought and Reality is applied to uncover the main character’s personality through his/her language use. The method used of this research was qualitative method and after that the data were classified based on the main theories from Saussure’s (1916) – Theory of Linguistics Whorf (1956) – Language, Thought and Reality and support with the theories from Schultz’s (2005) book entitled– Theories of Personality. Those theories used in this research to uncover the main character’s personality through his/her language use along the story. The result of this analysis based on Saussure’s theory shows that there is an internal factor from Hazel Grace itself is pessimistic. It’s shown by Hazel Graze describes herself in several symbols that show a different meaning from the actual meaning. In addition, based on Schultz’s theories, Hazel Grace is an introvert girl.